The reduction of intraocular pressure after instillation of travoprost compared with timolol in chronic primary angle-closure glaucoma (Medical Journal of Indonesia, 2006)
The objective of this study is to compare the reduction of intraocular pressure (IOP) after instillation of Travoprost compared with timolol in chronic primary angle-closure glaucoma. A prospective randomized, crossover study was conducted from April 2005 to July 2005 at Department of Ophthalmology, National Central General Hospital (RSCM) Jakarta on subjects with chronic primary angle-closure glaucoma. Subjects were randomly divided into 2 groups: those taking Travoprost once daily and those taking timolol twice daily. Two weeks after treatment with the first drug, the second drug was substituted. Intraocular pressure was recorded before therapy, at day 1, day 7, and day 14. There was a wash out period of three weeks prior to initial treatment and after the cross over. Sixteen subjects (32 eyes) met the inclusion criteria and were included in this study. The mean baseline IOP in the Travoprost group was 25.38 ± 3.01 mmHg, while in the timolol group it was 25.88 ± 2.55 mmHg (p=0.354). At day 7, the IOP were consecutively 16.75 ± 1.92 mmHg and 21.25 ± 3.09 mmHg (p=0.001) and at day 14 IOP were 13.94 ± 2.02 mmHg and 19.25 ± 2.18 mmHg (p=000). This showed that Travoprost decreased the IOP faster and greater than timolol. The mean baseline IOP was 25.38 ± 3.01 mmHg was decreased to 11.44 ± 1.90 mmHg with Travoprost. In the timolol group, the mean baseline IOP of 25.88 ± 2.55 mmHg was decreased to 6.63 ± 2.25 mmHg. Statistically, Travoprost significantly reduced the IOP faster and greater than timolol (p<0.05). Travoprost eye drops reduced the IOP faster and greater than timolol. (Med J Indones 2006; 15:242-5)